Traveling to violence: the case for a mobility-based spatial typology of homicide - Tita, George E. (Journal of research in crime and delinquency, 2005)
According to routine activities theory, crime is the result of an intersection between victims and offenders in both time and space. We introduce a spatial typology that identifies five combinations of victim and offender mobility to homicide incident locations: internal, predatory, intrusion, offense mobility, and total mobility types. The authors' argue that the joint mobility pattern of the victim and offender is the mechanism underlying routine activities theory, and made explicit by the spatial typology. Using information on the 420 homicides in Pittsburgh, Pennsylvania, between 1987 and 1995, we demonstrate that the majority of homicides involve at least some mobility on the part of victims and/or offenders. Our results also indicate that mobility to homicide incident locations is most associated with event characteristics such as motive, rather than with characteristics of the participants. With most offenders committing the homicide outside of their own neighborhood, levels of lethal violence in a community are influenced more by the interaction among nonlocal participants than by the violent actions of local residents. [ABSTRACT FROM AUTHOR]